2007
DOI: 10.1111/j.1365-2052.2007.01653.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphisms in the insulin‐like growth factor 1 receptor (IGF1R) gene from Japanese quail selected for body weight

Abstract: Insulin-like growth factor 1 receptor (IGF1R) is essential for the signalling of growth. In this study, we performed single nucleotide polymorphism (SNP) detection in the Japanese quail IGF1R coding region and an association study between SNPs and body weight in two lines (SS and LL) selected for large and small body weight. Of 21 SNPs obtained, a SNP at position AB292766:c.2293G>A led to the replacement of a valine with an isoleucine (V765I). The two lines were fixed for alternate alleles, with allele encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…Since by using PCR-RFLP method the presence or absence of a restriction site is detected, two alleles are expected at a particular site [24][25][26] . However, if there are two …”
Section: Discussionmentioning
confidence: 99%
“…Since by using PCR-RFLP method the presence or absence of a restriction site is detected, two alleles are expected at a particular site [24][25][26] . However, if there are two …”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 novel polymorphisms of the IGF-1R gene were detected in the Egyptian water buffalo by El-Magd et al (2013). Moe et al (2007) specified the existence of 21 SNPs by sequence comparison of the IGF1R coding region between LL and SS birds. Three SNPs (G26333A, G263336A, and C26639T) were detected in exon 2 of IGF-1R in Jinghai Yellow chickens by Yang et al (2012).…”
Section: Polymorphisms Of the Igf-1r Genementioning
confidence: 99%
“…To detect loci that affect growth traits in the Japanese quail, we used an F 2 population from an intercross between the LL and SS lines that was constructed previously by Moe et al (2007). The F 2 generation, which had 75 males and 74 females, was generated by mating a single F 1 male with two F 1 females.…”
Section: Detection Of Loci That Affect Growth Traits In the Japanese mentioning
confidence: 99%
“…Recently, we reported that a nonsynonymous single nucleotide polymorphism (SNP) in the gene for insulin-like growth factor 1 receptor (IGF1R) was associated with body weight in the LL and SS lines (Moe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%